Optical orientation mapping of additively manufactured alloys using directional reflectance microscopy - Matteo, Seita (2023)
One of the defining features of fusion-based additive manufacturing (AM) processes is the localized melting of metals by a high-energy source, which fuses the material together point by point and layer by layer into a three-dimensional part [4]. The directional thermal gradients, variable cooling rates, and cyclic re-heating which characterize these melting events are often conducive to parts with spatially varying microstructures [5]. This structural heterogeneity is a double-edged sword. If uncontrolled, it leads to components with variable mechanical properties and difficult-to-predict performance and lifetime [6]. The hindered adoption of additive technologies in industrial applications is a direct consequence of that. Conversely, the deliberate introduction of site-specific structural heterogeneities in metals produced by AM can be used as a design feature to enhance their mechanical properties [7], or to add extra functionalities that are not achievable by conventional means [8].